2023
DOI: 10.21474/ijar01/16222
|View full text |Cite
|
Sign up to set email alerts
|

Study of Prevalence of Hyperhomocysteinemia in Chronic Kidney Diseasepatients at Tertiary Care Hospital in Northwest Maharashtra

Abstract: Introduction-Chronic Kidney Disease is growing problem across all over world and India as well. Chronic kidney disease encompasses a spectrum of different pathophysiological processes associated with abnormal kidney function and a progressive decline in glomerular filtration rate(GFR).The risk for cardiovascular disease (CVD) morbidity and mortality remains high in all stages of CKD, including in patients with hemodialysis. More patients with CKD die of CVD than of the progression of kidney failure.The increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We found that in STEMI, 52 had no electrolyte abnormality, 12 were hypokalemic and in NSTEMI, 12 had no electrolyte abnormality and 4 had hypokalemia. Patil et al [15] determined the relation between in hospital mortality and electrolyte changes in cases and controls. Cases Included 100 clinically diagnosed and angiographically proven cases of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in STEMI, 52 had no electrolyte abnormality, 12 were hypokalemic and in NSTEMI, 12 had no electrolyte abnormality and 4 had hypokalemia. Patil et al [15] determined the relation between in hospital mortality and electrolyte changes in cases and controls. Cases Included 100 clinically diagnosed and angiographically proven cases of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…There was adequate knowledge regarding the risk of disease transmission through biomedical waste in all the groups except the sweepers". Patil et al [14] concluded that "the biomedical waste has been a growing concern due to increased awareness in public regarding infectious diseases. Good biomedical waste disposal practices lead to reduction in medical expenditure, unsightly scenes at various disposal bins and dumping sites.…”
Section: Awareness About the Legislations Regarding Bio-medical Waste...mentioning
confidence: 99%